2019
DOI: 10.14715/cmb/2019.65.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic copper exposure elicit neurotoxic responses in rat brain: Assessment of 8-hydroxy-2-deoxyguanosine activity, oxidative stress and neurobehavioral parameters

Abstract: Copper (Cu), one of the essential transition metal acts as a prosthetic group for variety of proteins and metalloenzymes. However, it may be hazardous when administered in excess. Copper induced memory impairment and progression of neurodegenerative diseases have not yet been fully elucidated. The aim of the present study was to investigate the effect of exposure to copper sulphate (10mg/kg and 20mg/kg body weight, daily for 16 weeks) on brain copper concentration, few biochemical parameters indicative of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Copper (Cu) can enter into cells though the copper transporter 1 ( 27 , 28 ). Excessive Cu accumulation in multiple organs (e.g., brain, kidney, heart, liver, and reproductive organs) due to both acute and chronic uptake causes potential toxic effects, including nephrotoxicity, hepatotoxicity, neurotoxicity and reproductive toxicity ( 4 , 10 , 11 , 29 31 ). In line with the previous studies ( 4 ), our current study showed that CuSO 4 exposure at the dose of 200 mg/kg/day for 28 days caused marked nephrotoxicity in mice, observed through the upregulation of serum BUN and CRE levels, as well as histopathological damage ( Figures 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Copper (Cu) can enter into cells though the copper transporter 1 ( 27 , 28 ). Excessive Cu accumulation in multiple organs (e.g., brain, kidney, heart, liver, and reproductive organs) due to both acute and chronic uptake causes potential toxic effects, including nephrotoxicity, hepatotoxicity, neurotoxicity and reproductive toxicity ( 4 , 10 , 11 , 29 31 ). In line with the previous studies ( 4 ), our current study showed that CuSO 4 exposure at the dose of 200 mg/kg/day for 28 days caused marked nephrotoxicity in mice, observed through the upregulation of serum BUN and CRE levels, as well as histopathological damage ( Figures 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports that mention the possible toxic effects of heavy metals, such as As, Cd, Pb, Hg, and Cu in CSVD associated disorders such as stroke, ischemia, dementia, amyloid angiopathy, etc. [39][40][41].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Similarly, as copper exposure induces oxidative stress, long‐term and excessive intake of copper may reduce the activities of various digestive enzymes in the intestine (Chen et al, ), decrease the rate of digestion, prolong chyme transit time in the intestine, enhance satiety and thus inhibit food intake (Gotteland, Araya, Pizarro, & Olivares, ; Sohal & Allen, ) as illustrated in Figure . Moreover, the antibacterial properties of high copper can change the microbial polymorphism of the pig's intestine (Di Giancamillo et al, ; Kumar et al, ; Papaioannou et al, ; Shurson et al, ; Zhang, Wu, et al, ), thereby influencing the composition of intestinal microbes. The change in the composition of intestinal microbial content may affect the utilization of cellulose in the gut and the regeneration of liver tissue, hence affecting the ability of the liver to secrete bile acids.…”
Section: Inhibitory Mechanism Of High Copper Supplementationmentioning
confidence: 99%
“…High copper supplementation in pig production has gained popularity and increased usage due to the ban on antibiotics use in some parts of the world (Adams et al, 2019;Che et al, 2018). Several studies have reported that high copper supplementation may not only regulate the activities of various enzymes such as digestive enzymes and antioxidant enzymes in pigs, but also may regulate the growth signalling pathways, feeding and fasting signalling pathways, and hence improve protein deposition and promote bone formation (Chen, Mayer, Weston, Bock, & Jumars, 2002;Kumar, Sathua, & Flora, 2019;Kumar, Kalita, Bora, & Misra, 2016a, 2016bKumar, Kalita, Misra, & Bora, 2015). In addition, studies have shown that the rational use of high copper diets may improve intestinal structure and function (Mei, Yu, Ju, Zhu, & Chen, 2009;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%